2015
DOI: 10.1162/jocn_a_00699
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Functional Architecture of Visual Word Recognition

Abstract: Abstract■ Despite a century of research into visual word recognition, basic questions remain unresolved about the functional architecture of the process that maps visual inputs from orthographic analysis onto lexical form and meaning and about the units of analysis in terms of which these processes are conducted. Here we use magnetoencephalography, supported by a masked priming behavioral study, to address these questions using contrasting sets of simple (walk), complex (swimmer), and pseudo-complex (corner) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 55 publications
6
23
1
Order By: Relevance
“…Behavioural masked priming studies for example, which have somewhat dominated the field of enquiry, have found consistent evidence for the decomposition of words with regular suffixation and pseudo-suffixation (e.g., teacher-TEACH; corner-CORN; Rastle, Davis, & New, 2004; see Rastle & Davis, 2008 for a review). Corresponding results have also been established in the neurophysiological literature, supporting decomposition of regularly derived (e.g., Solomyak & Marantz, 2010) irregularly derived (e.g., Stockall & Marantz, 2006) and pseudo-suffixed forms (e.g., Lewis, Solomyak, & Marantz, 2011;Whiting, Shtyrov, & Marslen-Wilson, 2014). This body of research indicates that comprehending a visual word entails decomposition into constituent morphemes, which are linked to abstract representations in the lexicon for processing.…”
Section: Routes To Word Recognitionsupporting
confidence: 64%
“…Behavioural masked priming studies for example, which have somewhat dominated the field of enquiry, have found consistent evidence for the decomposition of words with regular suffixation and pseudo-suffixation (e.g., teacher-TEACH; corner-CORN; Rastle, Davis, & New, 2004; see Rastle & Davis, 2008 for a review). Corresponding results have also been established in the neurophysiological literature, supporting decomposition of regularly derived (e.g., Solomyak & Marantz, 2010) irregularly derived (e.g., Stockall & Marantz, 2006) and pseudo-suffixed forms (e.g., Lewis, Solomyak, & Marantz, 2011;Whiting, Shtyrov, & Marslen-Wilson, 2014). This body of research indicates that comprehending a visual word entails decomposition into constituent morphemes, which are linked to abstract representations in the lexicon for processing.…”
Section: Routes To Word Recognitionsupporting
confidence: 64%
“…The effect seemed to stem from the descending slope following the peak of the evoked response. A similar result has previously been observed when contrasting consonant strings and (pseudo)words (Whiting et al, 2015). In that study, significant effects emerged between 155 and 230 ms, following the peak response centered at 150 ms.…”
Section: Discussionsupporting
confidence: 88%
“…However, several other studies have not been able to detect effects of morphology in the letter‐string response. Neither Vartiainen et al, (2009) using Finnish words or Whiting et al, (2015) using a similar contrast with English words found differences in the occipito‐temporal region between simple and complex words. Likewise, a study of morphological priming effects using French words by Cavalli et al (2016) did not reveal any significant effects of morphology in the posterior temporal cortex.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Morphologyspecific effects over and above form and meaning have been found along the ventral stream and in a vastly distributed network that includes left inferior and superior temporal gyri, left inferior frontal gyrus and left orbitofrontal gyrus (Cavalli, Colé, Badier, Zielinski, Chanoine, & Ziegler, 2016;Fruchter and Marantz, 2015;Whiting, Shtyrov, & Marslen-Wilson, 2015). In a recent MEG study using a primed lexical decision task, found evidence for a semantically driven morphological priming effect as early as 250 msec (i.e., M250) in left superior temporal gyrus.…”
Section: Introductionmentioning
confidence: 99%